Untangling factors influencing women entrepreneurs' involvement in tourism and its impact on sustainable tourism development - Sarminah Samad; Alaa Alharthi (Administrative Sciences, 2022)
Women's involvement in tourism has exerted an immense impact on the nation's economy. The low involvement of women in some countries has sparked the interest of scholars in investigating the factors that influence their involvement. The main purpose of this study was to examine the influence of self-efficacy (SE), perceptions of women's work (PWW), empowering leadership (EL), and psychological empowerment (PE) on tourism involvement. Consequently, the study determined the impact of tourism involvement in sustainable tourism development (STD). The population of the study was women entrepreneurs from the Saudi Arabia tourism industry. A total of 201 women participated in the study from the selected sample of 300, obtained through convenient sampling. For the data analysis, SPSS and PLS-SEM were employed. The results revealed that PWW, SE, EL, and PE significantly and positively influenced women entrepreneurs' involvement in tourism (WEIT). Further, WEIT significantly and positively impacted STD. This research is a pioneering work in which a research model was developed to incorporate PWW, SE, EL, PE, tourism involvement, and STD in light of social exchange theory and social identity theory. The findings provide implications for policymakers and academia and contribute to the existing body of knowledge on women's entrepreneurship, empowerment, tourism, and business management.
Keywords: 350; perception of women's work; self-efficacy; empowering leadership; psychological empowerment; tourism involvement; sustainable tourism development